2021
DOI: 10.3390/biom11060846
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Receptors in Spinal Nociceptive Control—An Update

Abstract: Diminished inhibitory control of spinal nociception is one of the major culprits of chronic pain states. Restoring proper synaptic inhibition is a well-established rational therapeutic approach explored by several pharmaceutical companies. A particular challenge arises from the need for site-specific intervention to avoid deleterious side effects such as sedation, addiction, or impaired motor control, which would arise from wide-range facilitation of inhibition. Specific targeting of glycinergic inhibition, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 73 publications
1
28
0
Order By: Relevance
“…It was hypothesized that a inhibition of GlyT1 might enhance glycinergic neurotransmission in the dorsal horn of the spinal cord. In this brain region, previous studies demonstrated a loss of synaptic inhibition, and this was suggested to contribute to the chronification of the facilitated pain perception observed in these animal models [ 54 ]. Indeed, GlyT1 active substances (both artificial substrates as well as inhibitors) showed anti-hyperalgesic and antiallodynic potential [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Genetical and Pharmacological Evidence For The Function Of I...mentioning
confidence: 99%
“…It was hypothesized that a inhibition of GlyT1 might enhance glycinergic neurotransmission in the dorsal horn of the spinal cord. In this brain region, previous studies demonstrated a loss of synaptic inhibition, and this was suggested to contribute to the chronification of the facilitated pain perception observed in these animal models [ 54 ]. Indeed, GlyT1 active substances (both artificial substrates as well as inhibitors) showed anti-hyperalgesic and antiallodynic potential [ 55 , 56 , 57 , 58 , 59 ].…”
Section: Genetical and Pharmacological Evidence For The Function Of I...mentioning
confidence: 99%
“…Normally, GABAergic neurons in laminae I-III of the spinal cord and in the ventral brainstem exert inhibitory effect on the Aβ-fibers (Agostinelli and Bassuk, 2021). Synaptic inhibition mediated by both glycinergic and GABAergic receptors at the dorsal horn of the spinal cord and in the related brainstem sites is deteriorated by many mechanisms evoked by peripheral inflammation or nerve injury (Agostinelli and Bassuk, 2021;Xing et al, 2021;Zeilhofer et al, 2021). The loss of GABAergic signaling following neuropathy could explain the hyper-stimulation of the Aβ-fibers that accompanies sciatic nerve injury, a process known as central sensitization (Kocot-Kępska et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The evidence discussed above has led to the development of pharmacological tools for the restoration of glycinergic activity. Recent studies have provided robust proof-of-concept that positive allosteric modulators (PAMs) of GlyRs exert anti-nociceptive effects on preclinical models of chronic pain ( Cioffi, 2017 ; Zeilhofer et al, 2018 , 2021 ). Thus, it is likely that the integration of basic research and translational approaches with focus on the glycinergic system may identify novel drugs against chronic pain.…”
Section: Glycinergic Neurotransmission In Chronic Painmentioning
confidence: 99%
“…Increasing evidence points to a critical role of dorsal horn α3-containing GlyRs in chronic inflammatory pain ( Zeilhofer et al, 2021 ; Figure 1C ). Initial electrophysiological studies showed that the activation of EP2 receptors (EP2-R) by prostaglandin E2 (PGE 2 ) decreased Gly-IPSCs in dorsal horn neurons through a PKA-dependent mechanism ( Ahmadi et al, 2002 ).…”
Section: Glycine Receptor Subtypes Involved In Nociception and Chroni...mentioning
confidence: 99%